Determinants of Health Service Efficiency in Hospital: A Systematic Review - Berly Nisa Srimayarti; Devid Leonard; Dicho Zhuhriano Yasli (International Journal of Engineering, Science and Information Technology, 2021)
One of the benchmarks for assessing service performance in hospitals is efficiency in medical services. Measurement of service  efficiency will affect the quality of the hospital. Patients will consider the completeness of the service facilities they have and the quality of services to be obtained. This is due to the tendency of people to seek quality health services. Improving service quality standards in hospitals will have an impact on increasing income and getting recognition from the community for the quality of services in hospitals. This study aims to look at the determinant factors that affect hospital efficiency. This study uses a systematic review method based on the PRISMA protocol. Article searches were conducted through four online databases (PubMed, ProQuest, SAGE and SpingerLink). The initial search found 307 articles, filtered using inclusion criteria, so as many as 8 articles were analyzed with a time span of 2017-2021. The efficiency of health services in hospitals is the basis for obtaining a wider patient base and producing quality services. The results of the literature study show that there are 29 factors affecting hospital efficiency. The various factors obtained were categorized into organizational factors, health resource factors, and technical efficiency factors.